The Effect of Perceived Organizational Support, Work Motivation, and Competence on Employee Performance Mediated by Employee Engagement - Dian Fetriah; Anik Hermingsih (Dinasti Publisher, 2023)
This study aims to analyze the effect of perceived organizational support, work motivation, and competence that can affect the performance of Spatial Planning Functional, both directly and mediated by employee engagement. The type of research is explanatory causality research. The quantitative method used is a proportionate stratified random sampling of 194 Spatial Planning Functional, data analysis method using SEM PLS with SmartPLS 3.2.9 software. The results of this study show that (1) perceived organizational support has a negative and insignificant effect on employee performance, (2) perceived organizational support has a positive and significant effect on employee engagement, (3) work motivation has a positive and significant influence on employee performance, (4) work motivation has a positive and significant influence on employee engagement, (5) competence has a positive and significant influence on employee performance, (6) competence has a positive and significant influence on employee engagement, (7) employee engagement mediates the effect of perceived organizational support on employee performance, (8) employee engagement mediates the effect of perceived organizational support on work motivation, (9) employee engagement mediates the effect of perceived organizational support on competence and (10) employee engagement has a positive and significant effect on employee performance.